(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Accordingly, ultrasonic measurements have been used by several authors to monitor the evolution of the viscoelastic moduli of polymers as a function of time or temperature and, recently, become a characterization technique of its own right, generally known as ultrasonic dynamic mechanical analysis (UDMA). Often the technique is used in conjunction with rheological methods as a means of providing a better insight into the viscoelastic behavior of polymer systems. As yet UDMA is underutilized primarily because of the low operating temperatures (usually below 100°C) of commercially available ultrasonic transducers, and also due to the requirement of a coupling medium to ensure an efficient energy transfer mechanism between the transducer and the test material. Despite these limitations, this paper shows that the use of ultrasonics is potentially a powerful method for the characterization of polymers, particularly as a tool for online monitoring of events occurring during polymer processing and in the manufacture of polymer matrix composites. The aim of this paper is to review the progress made in recent years, highlighting the potential and reliability of UDMA for monitoring physical transitions in polymers such as glass transition, melting, crystallization, as well as physical changes taking place during curing of thermosetting resins.